William Stanley, Charter and Ordinances of the City of Leavenworth 42 (1859) - (:unkn) unknown (My University, 1859)
§§ 1-2: Prohibited the carry of concealed weapons. Prohibited any person guilty of carrying a pistol, dirk, bowie-knife, colt, slung-shot, metal knuckles, or any other deadly weapon. Violators fined not less than five, nor more than two hundred dollars.
Keywords: CARRY; CARRY - CONCEALED